Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1111/petr.12641
|View full text |Cite
|
Sign up to set email alerts
|

Results of pediatric living donor compared to deceased donor liver transplantation in the PELD/MELD era: Experience from two centers on two different continents

Abstract: The LDLT option in the pediatric population allows recipients to be transplanted early. A total of 202 consecutive pediatric liver transplants from two different institutions--108 (LDLT) and 94 (DDLT)--were retrospectively compared. Overall, one- and three-yr patient and graft survival were similar between DDLT and LDLT. ACR was greater in recipients of DDLT at one and three yr (50.8% and 61.0%) compared to LDLT (30.8% and 32.2%) (p = 0.002). When the data were stratified according to PELD/MELD score, LDLT wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 16 publications
3
27
0
5
Order By: Relevance
“…Although some reports have found complication rates to have improved over time, these are usually reports from the 1990s, with the improvements seen by the early-to-mid 2000s[ 10 , 11 , 14 , 17 , 18 , 24 , 28 , 31 ]. This is similar to reports that have found that young age and smaller weight is no longer a risk factor for complications[ 2 , 8 , 13 , 14 , 16 - 18 , 22 , 26 , 27 , 29 , 31 ]. Indeed, we did not find that year or weight was an independent predictor of complication rates.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Although some reports have found complication rates to have improved over time, these are usually reports from the 1990s, with the improvements seen by the early-to-mid 2000s[ 10 , 11 , 14 , 17 , 18 , 24 , 28 , 31 ]. This is similar to reports that have found that young age and smaller weight is no longer a risk factor for complications[ 2 , 8 , 13 , 14 , 16 - 18 , 22 , 26 , 27 , 29 , 31 ]. Indeed, we did not find that year or weight was an independent predictor of complication rates.…”
Section: Discussionsupporting
confidence: 91%
“…The rates of HAT, PVT, and bile leak were higher than in most reports. For example, HAT is often in the range of 5%-10% (compared to our rate of 19%)[ 2 , 8 , 11 , 14 , 15 , 17 , 18 , 22 - 27 ], PVT in the range of 5%-15% (compared to our rate of 17%)[ 2 , 11 , 15 - 18 , 24 - 26 , 28 , 29 ], and bile leak in the range of 2%-15% (compared to our rate of 23%)[ 10 , 15 , 16 , 26 , 29 ]. A report from the SPLIT database found high rates of vascular complications (25%), PVT (16%), and bile leak (21%) in the 6.7% of recipients with complex vascular anomalies[ 30 ]; however, we did not find an association of abnormal anatomy comments and thrombosis or severe complications.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Initially, reported overall graft and patient survival in LDLT compared to DDLT were similar, but more recently, data have suggested that LDLT results in superior outcomes in both adult and pediatric patients. [5][6][7][8][9][10][11] Indeed, in many centers in Asia, Europe, and Canada, the majority of pediatric LT recipients undergo LDLT. 4,[12][13][14][15] The factors which result in superior outcomes with LDLT versus DDLT have not been well characterized.…”
Section: Improved Outcome S In Ldltmentioning
confidence: 99%